A smart traffic light modeling using AnyLogic simulation - Ajra, Husnul; Islam, Md. Shohidul; Mazlina, Abdul Majid; Tabassum, Noshin; Azlee, Zabidi (IEEE, 2026)
Urban traffic congestion remains a persistent issue in modern cities, often exacerbated by traditional traffic signal systems that operate on static cycles, disregarding real-time traffic conditions. This study presents a dynamic and smart traffic light control model using AnyLogic simulation software, leveraging discrete event simulation principles. The proposed model simulates a three-way urban intersection with directional flows from the west, east, and south, incorporating both car and bus agents governed by adaptive signal timing logic. By integrating the Road Traffic Library in AnyLogic, the system evaluates traffic density and adjusts green light durations based on vehicle queue and flow patterns. The simulation environment enables the modeling of complex behaviors such as lane selection, queuing, and pedestrian crossing interactions. Results demonstrate improved intersection efficiency through reduced vehicle wait times and balanced traffic flow across all directions. The 3D visualization further enhances the validation of traffic behavior and signal phase coordination in real-time. The findings emphasize the potential of simulation-based models as decision support tools in designing smart transportation systems geared towards smart cities.